Electron beam energy QA — a note on measurement tolerances. (8th March 2016) - Meyer, Juergen; Nyflot, Matthew J.; Smith, Wade P.; Wootton, Landon S.; Young, Lori; Yang, Fei; Kim, Minsun; Hendrickson, Kristi R. G.; Ford, Eric; Kalet, Alan M.; Cao, Ning; Dempsey, Claire; et al.
Abstract : Monthly QA is recommended to verify the constancy of high‐energy electron beams generated for clinical use by linear accelerators. The tolerances are defined as 2 % / 2 mm in beam penetration according to AAPM task group report 142. The practical implementation is typically achieved by measuring the ratio of readings at two different depths, preferably near the depth of maximum dose and at the depth corresponding to half the dose maximum. Based on beam commissioning data, we show that the relationship between the ranges of energy ratios for different electron energies is highly nonlinear. We provide a formalism that translates measurement deviations in the reference ratios into change in beam penetration for electron energies for six Elekta (6‐18 MeV) and eight Varian (6‐22 MeV) electron beams. Experimental checks were conducted for each Elekta energy to compare calculated values with measurements, and it was shown that they are in agreement. For example, for a 6 MeV beam a deviation in the measured ionization ratio of ± 15 % might still be acceptable (i.e., be within ± 2 mm ), whereas for an 18 MeV beam the corresponding tolerance might be ± 6 % . These values strongly depend on the initial ratio chosen. In summary, the relationship between differences of the ionization ratio and the corresponding beam energy are derived. The findings can be translated into acceptable tolerance values for monthly QA of electron beam energies. PACS number(s): 87.55, 87.56